A 3-Biomarker 2-Point-Based Risk Stratification Strategy in Acute Heart Failure - Álvarez-García, Jesús; García-Osuna, Álvaro; Vives-Borrás, Miquel; Ferrero-Gregori, Andreu; Martínez-Sellés, Manuel; Vázquez, Rafael; González-Juanatey, José R.; Rivera, Miguel; Segovia, Javier; Pascual-Figal, Domingo; Bover, Ramón; Bascompte, Ramón; et al. (Frontiers in Physiology, 2021)
Introduction and objectives: Most multi-biomarker strategies in acute heart failure (HF) have only measured biomarkers in a single-point time. This study aimed to evaluate the prognostic yielding of NT-proBNP, hsTnT, Cys-C, hs-CRP, GDF15, and GAL-3 in HF patients both at admission and discharge. Methods: We included 830 patients enrolled consecutively in a prospective multicenter registry. Primary outcome was 12-month mortality. The gain in the C-index, calibration, net reclassification improvement (NRI), and integrated discrimination improvement (IDI) was calculated after adding each individual biomarker value or their combination on top of the best clinical model developed in this study (C-index 0.752, 0.715-0.789) and also on top of 4 currently used scores (MAGGIC, GWTG-HF, Redin-SCORE, BCN-bioHF). Results: After 12-month, death occurred in 154 (18.5%) cases. On top of the best clinical model, the addition of NT-proBNP, hs-CRP, and GDF-15 above the respective cutoff point at admission and discharge and their delta during compensation improved the C-index to 0.782 (0.747-0.817), IDI by 5% (p<0.001), and NRI by 57% (p<0.001) for 12-month mortality. A 4-risk grading categories for 12-month mortality (11.7%, 19.2%, 26.7%, and 39.4%, respectively; p<0.001) were obtained using combination of these biomarkers. Conclusions: A model including NT-proBNP, hs-CRP, and GDF-15 measured at admission and discharge afforded a mortality risk prediction greater than our clinical model and also better than the most currently used scores. In addition, this 3-biomarker panel defined 4-risk categories for 12-month mortality.